Self-assembly thin films for sensing - Miyazaki, Celina Massumi; De Barros, Anerise; Mascagni, Daniela Branco Tavares [UNESP]; Graça, Juliana Santos; Campos, Paula Pereira [UNESP]; Ferreira, Marystela (Springer Nature, 2016)
The ability to control properties of nanomaterials by immobilization on a substrate of interest through Layer-by-Layer (LbL) and Langmuir-Blodgett (LB) techniques have drawn attention among many researchers. The molecular level control achieved by the LB and LbL techniques in coating surfaces can be explored in different areas, as energy generation and storage, environmental, clinical analysis, among others. We focus on three materials of great importance in the development of sensors in recent decades: metallic nanoparticles, graphene and carbon nanotubes based materials. In this chapter, the LB and LbL techniques are briefly discussed. The state-of-the-art of metal nanoparticles, graphene, and carbon nanotubes based materials in such films focusing sensing applications are summarized in this chapter.
Keywords: Carbon nanotubes; Graphene; Langmuir-Blodgett; Layer-by-Layer; Metal nanoparticles; Self-assembly; Thin films